Strategi Guru Kelas Dalam Membimbing Peserta Didik Berkesulitan Membaca: (Studi Kasus Pada Peserta Didik Kelas IV MIN 18 Aceh Barat) - Aidil Saputra; Sy. Rohana; Nurul Ulfa (Seutia Hukamaa Cendekia, 2024)
This study aims to find out the classroom teacher's strategy in guiding students with reading difficulties in grade IV MIN 18 Aceh Barat and how the classroom teacher's obstacles in guiding students with reading difficulties in grade IV MIN 18 Aceh Barat. This research is classified as a type of descriptive qualitative research. The subjects in this study are grade IV students who have difficulty reading, grade IV teachers, the Head of MIN 18 Aceh Barat, and Students' Parents. Data collection was carried out using interviews, observations, and documentation. Activities in data analysis are data collection, data reduction, data presentation, and conclusion. Based on the research results, the classroom teacher's strategy here is to use a special method for children who have difficulty reading, such as the Fernald method. Using various kinds of media in guiding children with reading difficulties. And also provide special guidance to teach him to read during empty hours or breaks. The obstacles for classroom teachers in guiding students with reading difficulties are students who do not know letters, only memorizing letters based on alphabetical order. In addition, environmental and hereditary factors are also obstacles for classroom teachers in guiding grade IV students of MIN 18 Aceh Barat who have difficulty reading.